The Effect of Compensation, Leadership Style, Leader Member Exchange and Organizational Citizenship Behavior on Performance - Suprianto, Ghalib; Taurisma Lajaria, Ridha; Naim, Ifin; Umar, Umar (International Journal of Management and Education in Human Development, 2022)
The purpose of this study was to examine and analyze the effect of compensation, leadership style, Leader Member Exchange and Organizational Citizenship Behavior on performance. This research was conducted on Beast Meat Employees in Kendari City. The population used was 35 Kendari City Beast Meat Employees. Data collection is done through interviews. The analytical tool used is multiple linear regression techniques. The results of the analysis show that compensation has a positive and significant effect on performance, leadership style has a positive but not significant effect on performance. This shows how leadership style is not related or not significant with the performance of Beast Meat Employees in Kendari City, related to the performance of Beast Meat Employees in Kendari City who need authoritarian support and cannot be involved in the decision-making process. The compensation variable has a positive and significant effect on performance. This shows that fair and proper assistance needs to be given to Kendari City Beast Meat Employees, the need for employees will increase significantly. Leader Member Exchange has a positive and significant effect on performance. Organizational Citizenship Behavior has a positive and significant effect on performance.